Journal of medieval military history. - Rogers, Clifford J.; DeVries, Kelly, 1956-; France, John (The Boydell Press, 2016)
This volume has a special focus on the topic of proxy actors and irregular forces in medieval warfare. John France and Jochen G. Schenk offer broad overviews: France addresses the military role of non-noble combatants and the significance of differences between medieval and modern ideas of the "legitimacy" of war-fighters, while Schenk applies a concept originating in political science - Mary Kaldor's idea of "New Wars"--To the conflicts of the Middle Ages, showing that in some ways, what is old is new again. Alex Mallett likewise ties the past to the present, comparing Muslim responses to the Crusades with modern responses to the Western-led invasion of Iraq in 2003. Michael Lower and Mike Carr, meanwhile, examine important groups of foreign fighters employed by North African states and Byzantium. In addition, the volume encompasses a study of Anglo-Norman siege engines (by Michael Fulton), three pieces on war and politics in fourteenth-century Iberia (by Douglas Biggs, Donald Kagay, and L.J. Andrew Villalon), and David Green's magisterial survey of imperial policy and military practice in the Plantagenet dominions in the fourteenth and fifteenth centuries. Contributors: Douglas Biggs, Mike Carr, Michael S. Fulton, David Green, Donald Kagay, Michael Lower, Alex Mallett, Jochen Schenk, Andrew Villalon